Why do African countries underinvest in agricultural R&D? - Benin, Samuel; McBride, Linden; Mogues, Tewodaj (International Food Policy Research Institute, 2016)
The approach to the analysis presented in this chapter is to examine the political economy of underinvestment in agricultural R&D using a framework of the key drivers of public investment decisionmaking (Mogues 2015): (1) the attributability of investments to key actors, including politicians, bureaucrats, interest groups, and donors; (2) the incentives and constraints of these actors; (3) the budget process; and (4) the political and economic governance environment. The chapter begins by presenting past trends in and future commitments to public agricultural research expenditures compared with other types of PAEs in different parts of Africa. As a means of understanding the resource constraints within which agricultural research expenditures are made, the analysis includes a discussion of trends in total expenditures and PAEs, which also serves as a review of the current progress in meeting the 2003 Maputo Declaration target of investing 10 percent of total national expenditures in the agricultural sector (NEPAD 2005). This discussion is followed by a review of the evidence on the returns to public investment in agricultural R&D compared with other types of public agricultural investments, and a discussion of the political economy drivers of underinvestment in agricultural R&D. Finally, conclusions are drawn in the context of understanding